Evaluation of Genotoxic Effects of Silver Nanoparticles on Bone Marrow Chromosome Aberrations in Laboratory Male Albino Mice Mus musculus - Mahmood, Nwsiba Khalid; Ahmed, Mahmood Othman (Iraqi Journal of Science, 2024)
Several desirable properties of silver nanoparticles (AgNPs) have found extensive use in consumer and healthcare products. Due to their potential to penetrate the nucleus and harm genetic material, their adverse effects, however, are mostly unknown and appear inevitable. This study aimed to determine genotoxic potential of AgNPs using mitotic index (MI) and structural chromosome aberrations (SCA) test in bone marrow cells of Mus musculus male albino mice. Two generations were experimented in this study, the first and second generation. In the first generation, five groups of five male mice including control group were used and intraperitoneally (IP) injected with two doses of AgNPs (50 mg/kg and 150mg/kg) in one-time and two-time doses manner. Then two-time dosed 150 mg/kg group was left for breeding and their male progenies (described as second-generation group) were dissected for detecting whether that abnormality in the male parent will transmit to progenies or not. Bone marrow cells were taken 24 hours following the last treatment. The results showed that AgNPs exposure significantly increased (P ≤0.05) number of SCA and decreased (MI) compared to negative control. Centromere breaks and gaps, along with ring chromosomes, also were the most frequent chromosome aberrations. The results suggest that AgNPs may be able to cause SCA-mediated genotoxicity in mice, with declining MI ratio after increasing dose and injection frequency. Still regular monitoring of their possible health effects as well as further characterization of their genotoxicity is necessary.